Preparation method and application of hydrophobic composite carbon-based filler

By preparing hydrophobic composite carbon-based fillers and combining them with chlorobenzene degradation bacteria, the problem of poor treatment effect of chlorobenzene waste gas in the prior art is solved, and efficient chlorobenzene removal and microbial degradation effects are achieved.

CN119113941APending Publication Date: 2024-12-13ZHEJIANG OCEAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410793155.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-19
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control chlorobenzene waste gas in volatile organic compounds (VOCs), especially due to its chemical stability and poor treatment effect due to its complex components.

Method used

By adopting the preparation method of hydrophobic composite carbon-based filler, the sunflower rod fibers are acid-base modification and composite treatment, and chitosan and stearic acid are added to form a hydrophobic composite carbon-based filler with a high specific surface area, and The chlorobenzene degradation bacteria are combined and biodegradable.

Benefits of technology

It significantly improves the removal rate of chlorobenzene waste gas, extends the microbial survival cycle, enhances the degradation ability of high-concentration VOCs, and provides more efficient waste gas treatment effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119113941A_ABST
    Figure CN119113941A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of hydrophobic composite carbon-based filler. The preparation method comprises the following steps: firstly, preparing sunflower stem carbon-based filler, secondly, carrying out hydrophobic modification on the carbon-based filler, then adding the carbon-based filler into an inorganic salt solution, adding chlorobenzene degrading bacterium liquid, and measuring the degradation performance of the filler. Biomass materials are widely used due to the fact that the biomass materials are high in biocompatibility, environmentally friendly, good in degradation performance, large in storage capacity, low in cost, low in price, easy to obtain and excellent in physicochemical property. The prepared carbon-based filler (aerogel) is widely used as an adsorption functional material to adsorb pollutants in the air due to relatively high specific surface area and porosity, so that on one hand, the carbon-based filler has the characteristic of high adsorption capacity, and on the other hand, the carbon-based filler can be widely used as an environment-friendly material; and technical support can be provided for environmental governance and industrial sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of VOCs waste gas treatment, and specifically relates to a preparation method and application of a hydrophobic composite carbon-based filler. Background Art

[0002] Volatile organic compounds (VOCs) are precursors of ozone and secondary aerosols, which can cause potential harm to the environment and human health. CVOCs such as chlorobenzene are one of the main VOCs emitted by petrochemical enterprises. CVOCs have high emissions, strong toxicity, and high chemical stability. They can remain in the environment for a long time and have been listed as highly toxic and harmful emissions by many countries. There are many VOCs treatment technologies, which are mainly divided into recovery technologies (condensation, absorption, adsorption, membrane separation, etc.) and destruction technologies (combustion, photocatalytic degradation, biodegradation, low-temperature plasma technology and ozone catalytic oxidation technology). VOCs emission components are complex and diverse, and different industries have different VOCs treatment technologies. A single VOCs treatment technology is difficult to achieve its purpose due to its own limitations, and the combined use of multiple technologies further improves the VOCs degradation effect. The present invention firstly pre-treats the chlorobenzene waste gas by an adsorption method, and then further uses biodegradation technology for degradation treatment, which not only prolongs the survival period of microorganisms, but also alleviates the impact of high concentrations of VOCs on the biodegradation process. Compared with single microbial degradation, the combined treatment of adsorption and biodegradation improves the VOCs removal rate. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a preparation method and application of a hydrophobic composite carbon-based filler, which is specifically achieved through the following technical solutions:

[0004] A method for preparing a hydrophobic composite carbon-based filler, the preparation method comprising the following steps:

[0005] 1) Sunflower stalk pretreatment: Cut the sunflower stalk into small pieces and wash them with deionized water, then dry them in a 60°C forced air drying oven for 48 hours, and after cooling, crush them in a crusher and pass them through a 20-mesh sieve to obtain sunflower stalk crushed material;

[0006] 2) Acid-base modification of sunflower stalk crushed material: prepare NaOH solution and NaClO2 solution respectively; react the sunflower stalk crushed material in NaOH solution for 3 hours, filter the reaction solution and wash it with water until it is neutral, then transfer the sunflower stalk crushed material to NaClO2 solution for 3 hours, filter the reaction solution and wash it with water until it is neutral, sieve the sunflower stalk crushed material and soak it in anhydrous ethanol to remove moisture, then dry it in a blast drying oven at 60°C for 24 hours to obtain sunflower stalk fiber;

[0007] 3) Preparation of composite carbon-based filler: add water and chitosan to the sunflower stalk fiber obtained in step 2), stir at a rate of 600 r / min for 3 h, pour the solution into a mold, absorb excess water, press with a weighing spoon to make it tight, then pre-freeze in a -20°C refrigerator for 24 h, and then dry in a freeze dryer for 48 h to obtain a composite carbon-based filler;

[0008] 4) Hydrophobic modification of composite carbon-based filler: Add a certain amount of stearic acid to anhydrous ethanol and dissolve it by ultrasonic. Soak the composite carbon-based filler prepared in step 3) in anhydrous ethanol with stearic acid for 4 hours, take it out, and dry it at 60°C for 24 hours to obtain a hydrophobic composite carbon-based filler.

[0009] Furthermore, in step 2), the concentration of the NaOH solution is 1.25 mol / L, the concentration of the NaClO2 solution is 0.55 mol / L, and the pH is 5.

[0010] Furthermore, in step 3), the mass ratio of sunflower stalk fiber to water is 3:25; the mass ratio of sunflower stalk fiber to chitosan is 6:1.

[0011] Furthermore, in step 3), the mold is a 48-well cell culture plate.

[0012] Furthermore, in step 4), a certain amount of stearic acid is added to anhydrous ethanol, specifically, the added proportion of stearic acid in 30g of anhydrous ethanol accounts for 1% of the mass of anhydrous ethanol.

[0013] Application of the hydrophobic composite carbon-based filler prepared by the above preparation method in the degradation of chlorobenzene waste gas.

[0014] Furthermore, the specific steps of chlorobenzene waste gas degradation are: adding the hydrophobic composite carbon-based filler to the sterilized inorganic salt, adding chlorobenzene degradation bacteria solution, and adjusting the initial OD of the solution to 600 =0.01, to degrade chlorobenzene waste gas.

[0015] Furthermore, the chlorobenzene degrading bacteria strain is RoseburiaHY-9, and the culture medium of the chlorobenzene degrading bacteria is inorganic salt, which includes the following components: Na2HPO4 4.0-5.0g / L, KH2PO4 0.8-1.2g / L, (NH4)2SO42.3-2.8g / L, MgSO4 0.18-0.23g / L, CaCl2 0.022-0.24g / L, trace element mother solution 0.8-1.2mL / L, and the solvent is deionized water.

[0016] Furthermore, the trace element mother solution includes the following components: FeSO4 0.8~1.2g / L, CuSO4 0.015~0.025g / L, H3BO3 0.013~0.015g / L, MnSO4 0.08~0.13g / L, ZnSO4 0.08~0.13g / L, Na2MoO4 0.015~0.025g / L, CoCl2 0.015~0.025g / L, and the solvent is deionized water.

[0017] The hydrophobic composite carbon-based filler prepared by the preparation method of the present invention has a high specific surface area, is easy for microorganisms to attach, is environmentally friendly, can increase the rate at which microorganisms degrade pollutants, and provides technical support for the waste gas treatment industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The actual pictures are of carbon-based fillers prepared by adding sunflower stalk fibers and deionized water in different proportions according to the method of the present invention, and the pictures represent the mass ratios of 3:50, 3:35, and 3:25 respectively;

[0019] Figure 2 It is a physical picture of the composite carbon-based filler prepared in Example 1 and the carbon-based filler prepared in Comparative Example 5;

[0020] Figure 3 yes Figure 2 The actual picture shows the effect after adding deionized water;

[0021] Figure 4 The products obtained in Example 1, Comparative Example 1 and Comparative Example 4 are curves showing the change of chlorobenzene with an initial concentration of 110 mg / L over time under laboratory shake flask conditions;

[0022] Figure 5 The carbon dioxide concentration in the headspace reaction of the shake flask during the degradation of 110 mg / L chlorobenzene by the hydrophobic carbon-based filler prepared in Example 1 and the product of Comparative Example 1;

[0023] Figure 6 The hydrophobic carbon-based fillers prepared in Example 1 and Comparative Examples 6 and 7 are curves showing the change of chlorobenzene with an initial concentration of 110 mg / L over time under the action of different amounts of stearic acid added;

[0024] Figure 7 The prepared carbon-based filler is shown in the FT-IR analysis chart, wherein the sunflower stalk aerogel is a filler without chitosan; the composite filler is a carbon-based filler after chitosan is added; the modified ones all refer to the carbon-based filler prepared with 1% stearic acid added;

[0025] Figure 8The figure shows the adsorption of 110 mg / L chlorobenzene by different carbon-based fillers. The blank is the one with only inorganic salt solution added, the modified sunflower stalk aerogel is the aerogel without chitosan but modified with 1% stearic acid, and the composite aerogel is the aerogel with chitosan added and modified with 1% stearic acid.

[0026] Note: All aerogels and carbon-based fillers in the figure are considered to have the same meaning. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with the accompanying drawings in order to better understand the technical solution.

[0028] Example 1

[0029] 1. Preparation of hydrophobic composite carbon-based fillers

[0030] The sunflower stalks were cut and washed, dried, ground and sieved for use. 10g of sunflower stalk fiber was placed in 1.25mol / L NaOH and NaClO2 solution with pH 5 and concentration of 0.55mol / L, stirred and reacted for 3h. The reacted solution was washed to neutrality, sieved and placed in anhydrous ethanol for reaction for 4h and then dried. The sample with a mass ratio of 3:25 of sunflower stalk fiber and water after the above treatment was weighed, and chitosan with a mass ratio of 6:1 of sunflower stalk fiber and chitosan was added at the same time. After continuous stirring and reaction for 3h, it was poured into a 48-well plate mold and freeze-dried for 48h to preliminarily obtain a composite sunflower stalk fiber carbon-based filler. Subsequently, the filler was placed in 30g anhydrous ethanol with 1% stearic acid added, soaked for 4h, taken out, and dried to obtain a hydrophobically modified sunflower stalk fiber carbon-based filler.

[0031] 2. Preparation of Chlorobenzene Degrading Bacteria Liquid

[0032] The purified RoseburiaHY-9 chlorobenzene efficient degrading bacteria were inoculated into a 250ml serum bottle containing 50ml inorganic salt medium. The culture was carried out at 30℃ and 160r / min for 48h. The bacterial solution was centrifuged at 8000r / min and 4℃ for 15min, and the sterilized inorganic salt solution was added to obtain a purified bacterial suspension. The OD was adjusted. 600The inorganic salt medium used for the culture of RoseburiaHY-9 contains the following components by mass: Na2HPO4 4.0-5.0 g / L, KH2PO4 0.8-1.2 g / L, (NH4)2SO4 2.3-2.8 g / L, MgSO4 0.18-0.23 g / L, CaCl2 0.022-0.24 g / L, and trace element mother solution 0.8-1.2 mL / L. The trace element mother solution comprises the following components: FeSO4 0.8-1.2 g / L, CuSO4 0.015-0.025 g / L, H3BO3 0.013-0.015 g / L, MnSO4 0.08-0.13 g / L, ZnSO4 0.08-0.13 g / L, Na2MoO4 0.015-0.025 g / L, and CoCl2 0.015-0.025 g / L.

[0033] 3. Degradation performance test

[0034] The hydrophobically modified sunflower stalk fiber carbon-based filler prepared above was placed in 50 ml of sterilized inorganic salt, chlorobenzene-degrading bacteria HY-9 was added, and the initial OD of the inorganic salt was adjusted. 600 The concentration of chlorobenzene was 0.01, 110 mg / L chlorobenzene was added, and the mixture was cultured in a shaker at 30°C and 160 r / min, and then its degradation was determined.

[0035] Comparative Example 1

[0036] Add OD to 50 ml of sterilized inorganic salt solution. 600 The initial OD of the inorganic salt solution was adjusted to 1.0 for the chlorobenzene-degrading bacterial solution. 600 = 0.01, add 110 mg / L chlorobenzene, place in a shaker at 30°C and 160 r / min, and then measure its degradation

[0037] Comparative Example 2

[0038] Add an appropriate amount of substrate to 50 ml of the sterilized inorganic salt solution and adjust the substrate concentration of chlorobenzene to 110 mg / L.

[0039] Comparative Example 3: Preparation of sunflower stalk aerogel without adding chitosan

[0040] The sunflower stalks were cut into segments, washed, dried, ground and sieved for later use; 10 g of sunflower stalk fiber was placed in 1.25 mol / L NaOH and NaClO2 solution with a pH of 5 and a concentration of 0.55 mol / L, and stirred for reaction for 3 hours; the reacted solution was washed to neutrality, sieved, placed in anhydrous ethanol for reaction for 4 hours and then dried; a sample with a mass ratio of 3:25 of the treated sunflower stalk fiber to water was weighed, and after continuous stirring for reaction for 3 hours, it was poured into a 48-well plate mold and freeze-dried for 48 hours to initially obtain aerogel.

[0041] Comparative Example 4: Preparation of modified sunflower straw carbon-based filler (aerogel) without adding chitosan

[0042] 1. Preparation of sunflower stalk aerogel: Wash, dry, grind and sieve the cut sunflower stalks for later use; Take 10g of sunflower stalk fiber and place it in NaOH and NaClO2 solution, stirring and reacting for 3h; Wash the reacted solution to neutrality, sieve it and place it in anhydrous ethanol for reaction for 4h and then dry it; Weigh the sample with a mass ratio of 3:25 of the treated sunflower stalk fiber to water, stir and react for 3h, pour it into a 48-well plate mold, freeze-dry for 48h, and preliminarily obtain aerogel. Then put the filler in 30g of anhydrous ethanol with 1% stearic acid added, soak it for 4h, take it out and dry it, and then obtain the hydrophobically modified sunflower stalk carbon-based filler (aerogel).

[0043] 2. Preparation of Chlorobenzene Degrading Bacterial Liquid

[0044] The purified RoseburiaHY-9 chlorobenzene efficient degrading bacteria were inoculated into a 250ml serum bottle containing 50ml inorganic salt medium. The culture was carried out at 30℃ and 160r / min for 48h. The bacterial solution was centrifuged at 8000r / min and 4℃ for 15min, and the sterilized inorganic salt solution was added to obtain a purified bacterial suspension. The OD was adjusted. 600 The inorganic salt medium used for the culture of RoseburiaHY-9 contains the following components by mass: Na2HPO4 4.0-5.0 g / L, KH2PO4 0.8-1.2 g / L, (NH4)2SO4 2.3-2.8 g / L, MgSO4 0.18-0.23 g / L, CaCl2 0.022-0.24 g / L, and trace element mother solution 0.8-1.2 mL / L. The trace element mother solution comprises the following components: FeSO4 0.8-1.2 g / L, CuSO4 0.015-0.025 g / L, H3BO3 0.013-0.015 g / L, MnSO4 0.08-0.13 g / L, ZnSO4 0.08-0.13 g / L, Na2MoO4 0.015-0.025 g / L, and CoCl2 0.015-0.025 g / L.

[0045] 3. Degradation performance test: Place the above aerogel in 50 ml of sterilized inorganic salt, add chlorobenzene degrading bacteria HY-9 bacterial solution, and adjust the initial OD of the inorganic salt. 600 The concentration of chlorobenzene was 0.01, 110 mg / L chlorobenzene was added, and the mixture was cultured in a shaker at 30°C and 160 r / min, and then its degradation was determined.

[0046] Comparative Example 5: Preparation of composite sunflower stalk fiber carbon-based filler (aerogel) by adding chitosan

[0047] The cut sunflower stalks were washed, dried, ground and sieved for later use; 10 g of sunflower stalk fiber was placed in NaOH and NaClO2 solutions, stirred and reacted for 3 h; the reacted solution was washed to neutrality, sieved and placed in anhydrous ethanol for reaction for 4 h and then dried; a sample with a mass ratio of 3:25 of sunflower stalk fiber and water after the above treatment was weighed, and chitosan with a mass ratio of 6:1 of sunflower stalk fiber and chitosan was added at the same time, and after continuous stirring and reaction for 3 h, the sample was poured into a 48-well plate mold and freeze-dried for 48 h to preliminarily obtain a composite sunflower stalk fiber carbon-based filler.

[0048] Comparative Example 6: 2% stearic acid was added to 30g anhydrous ethanol to prepare 2% (aerogel)

[0049] 1. Preparation of Sunflower Straw Aerogel

[0050] Wash and dry the cut sunflower stalks, grind and sieve for later use; take 10g of sunflower stalk fiber and place it in NaOH and NaClO2 solution, stir and react for 3h; wash the reacted solution to neutrality, sieve it and place it in anhydrous ethanol to react for 4h and then dry it; weigh the sample with a mass ratio of 3:25 of the treated sunflower stalk fiber and water, stir and react for 3h, pour it into a 48-well plate mold, freeze-dry for 48h, and preliminarily obtain aerogel. Then put the filler in 30g anhydrous ethanol with 2% stearic acid added, soak it for 4h, take it out, and dry it to obtain a hydrophobically modified sunflower stalk carbon-based filler (aerogel).

[0051] 2. Preparation of Chlorobenzene Degrading Bacterial Liquid

[0052] The purified RoseburiaHY-9 chlorobenzene efficient degrading bacteria were inoculated into a 250ml serum bottle containing 50ml inorganic salt medium. The culture was carried out at 30℃ and 160r / min for 48h. The bacterial solution was centrifuged at 8000r / min and 4℃ for 15min, and the sterilized inorganic salt solution was added to obtain a purified bacterial suspension. The OD was adjusted. 600The inorganic salt medium used for the culture of RoseburiaHY-9 contains the following components by mass: Na2HPO4 4.0-5.0 g / L, KH2PO4 0.8-1.2 g / L, (NH4)2SO4 2.3-2.8 g / L, MgSO4 0.18-0.23 g / L, CaCl2 0.022-0.24 g / L, and trace element mother solution 0.8-1.2 mL / L. The trace element mother solution comprises the following components: FeSO4 0.8-1.2 g / L, CuSO4 0.015-0.025 g / L, H3BO3 0.013-0.015 g / L, MnSO4 0.08-0.13 g / L, ZnSO4 0.08-0.13 g / L, Na2MoO4 0.015-0.025 g / L, and CoCl2 0.015-0.025 g / L.

[0053] 3. Degradation performance test

[0054] The aerogel was placed in 50 ml of sterilized inorganic salt, and the chlorobenzene-degrading bacteria HY-9 was added to adjust the initial OD of the inorganic salt. 600 The concentration of chlorobenzene was 0.01, 110 mg / L chlorobenzene was added, and the mixture was cultured in a shaker at 30°C and 160 r / min, and then its degradation was determined.

[0055] Comparative Example 7: 3% stearic acid was added to 30g anhydrous ethanol to prepare 3% (aerogel)

[0056] 1. Preparation of Sunflower Straw Aerogel

[0057] Wash and dry the cut sunflower stalks, grind and sieve for later use; take 10g of sunflower stalk fiber and place it in NaOH and NaClO2 solution, stirring and reacting for 3h; wash the reacted solution to neutrality, sieve it, place it in anhydrous ethanol, react for 4h and then dry it; weigh the sample with a mass ratio of 3:25 of the treated sunflower stalk fiber and water, stir and react for 3h, pour it into a 48-well plate mold, freeze-dry for 48h, and preliminarily obtain aerogel. Then put the filler in 30g anhydrous ethanol with 3% stearic acid added, soak it for 4h, take it out, and dry it to obtain a hydrophobically modified sunflower stalk carbon-based filler (aerogel).

[0058] 2. Preparation of Chlorobenzene Degrading Bacterial Liquid

[0059] The purified RoseburiaHY-9 chlorobenzene efficient degrading bacteria were inoculated into a 250ml serum bottle containing 50ml inorganic salt medium. The culture was carried out at 30℃ and 160r / min for 48h. The bacterial solution was centrifuged at 8000r / min and 4℃ for 15min, and the sterilized inorganic salt solution was added to obtain a purified bacterial suspension. The OD was adjusted. 600The inorganic salt medium used for the culture of RoseburiaHY-9 contains the following components by mass: Na2HPO4 4.0-5.0 g / L, KH2PO4 0.8-1.2 g / L, (NH4)2SO4 2.3-2.8 g / L, MgSO4 0.18-0.23 g / L, CaCl2 0.022-0.24 g / L, and trace element mother solution 0.8-1.2 mL / L. The trace element mother solution comprises the following components: FeSO4 0.8-1.2 g / L, CuSO4 0.015-0.025 g / L, H3BO3 0.013-0.015 g / L, MnSO4 0.08-0.13 g / L, ZnSO4 0.08-0.13 g / L, Na2MoO4 0.015-0.025 g / L, and CoCl2 0.015-0.025 g / L.

[0060] 3. Degradation performance test

[0061] The aerogel was placed in 50 ml of sterilized inorganic salt, and the chlorobenzene-degrading bacteria HY-9 was added to adjust the initial OD of the inorganic salt. 600 The above experiments were carried out under the same experimental conditions. The prepared carbon-based filler was added to a shake bottle containing 50 ml of sterilized inorganic salts, covered with a butyl rubber stopper and a bottle cap, and then the required volume of substrate was drawn from the brown substrate bottle using a substrate needle, and the substrate was added to the headspace of the shake bottle to control the initial chlorobenzene concentration of all groups to be 110 mg / L; the initial OD of all experimental groups was 600 All of them are 0.01 (control the biomass of all experimental groups to be the same); 3 parallel samples are set up for each group of experiments, cultured in a shaker at 30℃ and 160r / min for the same time, and the degradation effect is determined.

[0062] Degradation effect

[0063] Figure 1 (No chitosan added) is a photo of the carbon-based filler prepared by adding different mass ratios of sunflower stalk fiber and water. Figure 1 It can be seen that the final forming effect of the aerogel produced when the mass ratio of sunflower stalk fiber to water is 3:25 is the best.

[0064] Figure 2 This is a physical picture of the composite carbon-based filler after adding chitosan prepared according to the preparation method of the embodiment and according to comparative example 5.

[0065] Figure 3The figures are as follows: the composite carbon-based filler hydrophobically modified with 1% stearic acid and the composite carbon-based filler without stearic acid hydrophobic modification are added into deionized water. It is noteworthy that the carbon-based filler without stearic acid hydrophobic modification prepared in comparative example 5 is dissolved immediately after being added into deionized water and cannot meet the experimental requirements, while the composite carbon-based filler prepared in Example 1 of the present invention can still remain intact after being cultured in a shaker at 160 r / min for 24 hours.

[0066] Test results such as Figure 4 As shown, the results show that the experimental group of hydrophobic carbon-based fillers prepared by the present invention quickly starts the reaction in a short time and achieves 100% dechlorination efficiency at the end of the reaction. The removal load of the composite carbon-based filler prepared in Example 1 is 11.08 mg / (L·h), and the removal loads of Comparative Examples 1 and 4 are both 9.23 mg / (L·h). Figure 5 It can be seen that the concentration of carbon dioxide generated above the headspace in Example 1 is higher than that in Comparative Example 1.

[0067] Figure 6 The degradation of the composite carbon-based filler with different amounts of stearic acid added to Example 1, Comparative Examples 6 and 7 is shown. It can be seen that although the degradation is the same, the OD of the experimental group with 1% stearic acid modifier added to Example 1 is 600 This is greater than other addition amounts, which may be related to the action of microorganisms, so the default addition amount of stearic acid in subsequent experiments is 1% (unless otherwise specified). Figure 7 FT-IR analysis of four groups of carbon-based fillers, 2853 cm -1 The sharp peak that appears belongs to the CH bond stretching vibration absorption peak of stearic acid, indicating that stearic acid has successfully modified the composite carbon-based filler; while this peak does not appear after the carbon-based filler is modified without adding chitosan. It is speculated that the success of stearic acid modification is related to the addition of chitosan. Figure 8 The adsorption profiles of Example 1, Comparative Examples 2 and 4 at 110 mg / L (without bacteria added) are shown. The adsorption rate of Example 1 is higher than that of the two comparative examples. It is speculated that this may be one of the reasons why its degradation effect is better than that of the other comparative examples.

Claims

1. A method for preparing a hydrophobic composite carbon-based filler, characterized in that The preparation method comprises the following steps: 1) Sunflower stalk pretreatment: Cut the sunflower stalk into small pieces and wash them with deionized water, then dry them in a 60°C forced air drying oven for 48 hours, and after cooling, crush them in a crusher and pass them through a 20-mesh sieve to obtain sunflower stalk crushed material; 2) Acid-base modification of sunflower stalk crushed material: prepare NaOH solution and NaClO2 solution respectively; react the sunflower stalk crushed material in NaOH solution for 3 hours, filter the reaction solution and wash it with water until it is neutral, then transfer the sunflower stalk crushed material to NaClO2 solution for 3 hours, filter the reaction solution and wash it with water until it is neutral, sieve the sunflower stalk crushed material and soak it in anhydrous ethanol to remove moisture, then dry it in a blast drying oven at 60°C for 24 hours to obtain sunflower stalk fiber; 3) Preparation of composite carbon-based filler: add water and chitosan to the sunflower stalk fiber obtained in step 2), stir at a rate of 600 r / min for 3 h, pour the solution into a mold, absorb excess water, press with a weighing spoon to make it tight, then pre-freeze in a -20°C refrigerator for 24 h, and then dry in a freeze dryer for 48 h to obtain a composite carbon-based filler; 4) Hydrophobic modification of composite carbon-based filler: Add a certain amount of stearic acid to anhydrous ethanol and dissolve it by ultrasonic. Soak the composite carbon-based filler prepared in step 3) in anhydrous ethanol with stearic acid for 4 hours, take it out, and dry it at 60°C for 24 hours to obtain a hydrophobic composite carbon-based filler.

2. The method for preparing a hydrophobic composite carbon-based filler according to claim 1, characterized in that In step 2), the concentration of the NaOH solution is 1.25 mol / L, the concentration of the NaClO2 solution is 0.55 mol / L, and the pH is 5.

3. The method for preparing a hydrophobic composite carbon-based filler according to claim 1, characterized in that In step 3), the mass ratio of sunflower stalk fiber to water is 3:25; the mass ratio of sunflower stalk fiber to chitosan is 6:

1.

4. The method for preparing a hydrophobic composite carbon-based filler according to claim 1, characterized in that In step 3), the mold is a 48-well cell culture plate.

5. The method for preparing a hydrophobic composite carbon-based filler according to claim 1, characterized in that In step 4), a certain amount of stearic acid is added to anhydrous ethanol, specifically, the added proportion of stearic acid in 30g of anhydrous ethanol accounts for 1% of the mass of anhydrous ethanol.

6. Use of the hydrophobic composite carbon-based filler prepared by any preparation method of claims 1 to 5 in the degradation of chlorobenzene waste gas.

7. The use according to claim 6, characterized in that The specific steps of chlorobenzene waste gas degradation are: adding hydrophobic composite carbon-based filler to sterilized inorganic salt, adding chlorobenzene degradation bacteria solution, adjusting the initial OD of the solution 600 =0.01, to degrade chlorobenzene waste gas.

8. The use according to claim 7, characterized in that The chlorobenzene degrading bacteria strain is Roseburia HY-9, and the culture medium of the chlorobenzene degrading bacteria is inorganic salt, and the inorganic salt culture medium includes the following components: Na 2HPO4 4.0~5.0g / L, KH2PO4 0.8~1.2g / L, (NH4)2SO4 2.3~2.8g / L, MgSO4 0.18~0.23g / L, CaCl2 0.022~0.24g / L, trace element mother solution 0.8~1.2mL / L, the solvent is deionized water.

9. The use according to claim 8, characterized in that The trace element mother solution comprises the following components: FeSO4 0.8-1.2 g / L, CuSO4 0.015-0.025 g / L, H3BO3 0.013-0.015 g / L, MnSO4 0.08-0.13 g / L, ZnSO4 0.08-0.13 g / L, Na2MoO4 0.015-0.025 g / L, CoCl2 0.015-0.025 g / L, and the solvent is deionized water.